Elizabeth Oakes Prince Smith correspondence - Smith, Elizabeth Oakes Prince, 1806-1893.
ALS from Smith to music publishers Biglow & Main requesting songbooks and other supplies for her Sunday school in Carteret County, N.C.
Author, lecturer, and reformer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Biglow & Main; Music publishers; Songbooks; Sunday schools -- North Carolina -- Carteret County; Authors; Lecturers; Reformers